Echinococcus multilocularis in foxes and raccoon dogs: an increasing concern for Baltic countries - Bagrade, Guna (Parasit Vectors, 2016)
BACKGROUND: In Europe, the life-cycle of Echinococcus multilocularis is predominantly sylvatic, involving red foxes (Vulpes vulpes) as the main definitive hosts and rodents such as muskrats and arvicolids as intermediate hosts. The parasite is the etiological agent of human alveolar echinococcosis, a malignant zoonotic disease caused by the accidental ingestion of eggs shed by definitive hosts in their faeces. The aims of this study were to investigate the prevalence of E. multilocularis in red foxes and raccoon dogs (Nyctereutes procyonoides) and to study the environmental factors favouring the perpetuation of the parasite in Latvia. METHODS: A total of 538 red foxes and 407 raccoon dogs were collected across Latvia from 2010 to 2015. The sedimentation and counting technique was used for collecting E. multilocularis adult worms from fox and raccoon dog intestines. The morphological identification of the parasite was confirmed by molecular analysis. RESULTS: The prevalence of E. multilocularis was significantly higher in foxes (17.1%; intensity of infection 1–7,050 worms) (P < 0.001) than in raccoon dogs (8.1%; intensity of infection 5–815 worms). In foxes, a significant positive correlation (r ((10)) = 0.7952, P = 0.001) was found between parasite prevalence and the intensity of infection. A positive relationship (R (s) = 0.900, n = 5, P = 0.037) between parasite prevalence and precipitation was also observed. In raccoon dogs, a significant negative relationship (F ((1,8)) = 9.412, P = 0.015) between animal density and parasite prevalence, and a significant positive relationship (F ((1,8)) = 7.869, P = 0.023) between parasite prevalence and agricultural land cover, were detected. CONCLUSIONS: The results of this study confirm the red fox as the most important definitive host of E. multilocularis and, consequently, as the main target for control programmes in the Baltic countries. Raccoon dogs seem to play a secondary role in the life-cycle of E. multilocularis within the investigated European region. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1891-9) contains supplementary material, which is available to authorized users.